James In A Mess and Other Thomas the Tank Engine Stories. - Awdry, Rev. W. (New York, NY : Random House, 1993)
Sir Topham Hatt's railroad engines, Harold the helicopter, and Bertie the bus learn about good manners and hard work.
Keywords: Railroads - Trains - Fiction; Behavior - Fiction; Mitton, David, ill; McArthur, Kenny, ill; Permane, Terry, ill; Awdry, W. Railroad series; Thomas the Tank Engine and Friends